A Comparative Study of the Health Systems Performance Assessment Frameworks in the World - mahdiyeh heydari; leila doshmangir (Tehran University of Medical Sciences, 2019)
Background:  Need to assess the health system performance, various models and frameworks have been developed by different groups and organizations. This study explores health system performance assessment frameworks using the comparative-analytical study.   Materials and Methods: This is a comparative-descriptive study conducted using descriptive-prescriptive method based on comprehensive comparative analysis. The scope of research includes health system frameworks. The study results compared and interpreted based on identified factors in comparative tables.   Results:  Overall, 11 frameworks out of 16 ones described, analyzed and compared to each other. Some of the frameworks in addition to providing insight about the health system have focus on assessment of health system performance. Each framework follows especial goals which focus on importance the health systems assessment.   Conclusion: During the time, health system frameworks have changed and developed according to the health systems changes. Developed Frameworks in recent years are more comprehensive than others which have been presented at first. Utilizing these frameworks in order to identify health system goals, assess based on responsibility (organizational actions or outside the organizations) and ways to reach them can be effective. Using the developed frameworks based on their domains and objectives can be considered in health system performance.